2014
DOI: 10.1111/jog.12462
|View full text |Cite
|
Sign up to set email alerts
|

Expression of placenta growth factor, soluble fms‐like tyrosine kinase‐1, metal‐responsive transcription factor‐1, heme oxygenase 1 and hypoxia inducible factor‐1α mRNAs in pre‐eclampsia placenta and the effect of pre‐eclampsia sera on their expression of choriocarcinoma cells

Abstract: Changes in PlGF mRNA expression in pre-eclampsia placenta may relate to serum factors and the expression of MTF-1 and HIF-α mRNA. Changes in sFlt-1mRNA expression may relate to serum factors and the expression of HIF-α mRNA. We suggest that serum factors play a role in PlGF and sFlt-1 expression in pre-eclampsia placenta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…It should be noted that in pre-eclamptic (PE) pregnancies, the role of Nrf2 is somewhat more controversial. Studies have documented that placental Nrf2 levels are reduced in PE [106] and that Nrf2 target gene HO-1 is downregulated in placental trophoblast derived JEG-3 cells following exposure to PE serum [107]. Nrf2-dependent HO-1 expression can negatively regulate soluble fms-like tyrosine kinase-1 (sFlt-1) levels [107][108][109], with enhanced sFlt-1 strongly implicated in the pathogenesis of PE and the development of maternal hypertensive symptoms during pregnancy.…”
Section: Role Of Nrf2 In Pregnancymentioning
confidence: 98%
See 1 more Smart Citation
“…It should be noted that in pre-eclamptic (PE) pregnancies, the role of Nrf2 is somewhat more controversial. Studies have documented that placental Nrf2 levels are reduced in PE [106] and that Nrf2 target gene HO-1 is downregulated in placental trophoblast derived JEG-3 cells following exposure to PE serum [107]. Nrf2-dependent HO-1 expression can negatively regulate soluble fms-like tyrosine kinase-1 (sFlt-1) levels [107][108][109], with enhanced sFlt-1 strongly implicated in the pathogenesis of PE and the development of maternal hypertensive symptoms during pregnancy.…”
Section: Role Of Nrf2 In Pregnancymentioning
confidence: 98%
“…Studies have documented that placental Nrf2 levels are reduced in PE [106] and that Nrf2 target gene HO-1 is downregulated in placental trophoblast derived JEG-3 cells following exposure to PE serum [107]. Nrf2-dependent HO-1 expression can negatively regulate soluble fms-like tyrosine kinase-1 (sFlt-1) levels [107][108][109], with enhanced sFlt-1 strongly implicated in the pathogenesis of PE and the development of maternal hypertensive symptoms during pregnancy. Conversely, upregulation of Nrf2-dependent antioxidant defences specifically in cytotrophoblasts [110] or syncytiotrophoblasts [104] has been postulated to actively contribute to the increased shedding of syncytial knots (fused cytotrophoblasts and syncytiotrophoblasts) found to be raised in PE and implicated in maternal hypertension [110].…”
Section: Role Of Nrf2 In Pregnancymentioning
confidence: 98%
“…In preeclampsia pregnancies, the role of Nrf2 has been reported to be somehow controversial, whereas reduced expression of Nrf2 was noted in placental oxidative stress-induced preeclampsia [ 110 ]. Inappropriate regulation of Nrf2-based HO-1 expression mediates soluble fms-like typrsine kinase-1 (sFlt-1) [ 111 ]. Increased level of sFtl-1 has been recorded in the pathogenesis of PE and development of maternal hypertensive condition during pregnancy.…”
Section: Significant Impact Of Nrf2 Pathway On Pregnancymentioning
confidence: 99%
“…The cascade of events linking placental ischemia to maternal hypertension has been a subject of intense focus in our laboratory and others. While both placental and circulating levels of VEGF and PlGF are reduced in preeclamptic women, the levels of the VEGF/PlGF receptor sFlt-1 are elevated (27,102,143,161,193). By using the RUPP model, we have shown that placental ischemia/hypoxia elicits the release of sFlt-1 (58).…”
Section: Effects Of Obesity On the Release Of Soluble Placental Factorsmentioning
confidence: 99%